Research progress of Traditional Chinese Medicine in the adjuvant treatment of acute myeloid leukemia complicated with constipation (中药辅助治疗急性髓细胞白血病合并便秘的研究进展) - WANG Xue (王雪); CAO Hongjing (曹红京) (中西医结合护理)
Constipation is a common complication of chemotherapy in cancer patients. Complicated constipation imposes a serious risk of infection on patients undergoing chemotherapy for acute myelocytic leukemia (AMI), increases the difficulty in following treatment and nursing. Traditional Chinese Medicine has a positive effect in the adjuvant treatment of cancer and complicated constipation. This paper reviewed the studies on Traditional Chinese Medicine in the adjuvant treatment of AMI complicated with constipation, and provided reference for clinical practice. (便秘是肿瘤化疗患者常见并发症。急性髓细胞白血病(AML)患者并发便秘不仅会增加治疗和护理难度, 同时还可能加重感染, 不利于患者康复。中药在抗肿瘤和缓解便秘方面具有积极的作用。本研究就中药辅助治疗AML、改善便秘以及相关护理管理研究进展进行综述, 旨在为AML合并便秘治疗和护理提供参考。)